The Effects of Organizational Climate, Organizational Commitment, and Competence on Employee Performance at Breeze Garment in Denpasar - Dananjaya, I Kadek Dwi; Suardhika, I Nengah; Rihayana, I Gede (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
In the era of globalization, advances in science and technology have driven the rapid development of the global economy. These conditions require organizations to be able to improve human resource performance in order to remain competitive. This study aims to determine and analyze the influence of organizational climate, organizational commitment, and competence on employee performance at Breeze Garment in Denpasar. The sample size for this study consisted of 30 employees selected using a saturation sampling technique. Research data were collected via a questionnaire using a Likert scale and analyzed using the Statistical Program for Social Sciences (SPSS). The results indicate that organizational climate has a positive and significant effect on employee performance at Breeze Garment in Denpasar. Furthermore, organizational commitment and competence were also found to have a positive and significant effect on employee performance. Based on these findings, future researchers are advised to include additional variables that may influence employee performance and to expand the sample size, thereby yielding more comprehensive and accurate findings in the future.